If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + -7x + 6 = 0 Multiply x * x x2 + -7x + 6 = 0 Reorder the terms: 6 + -7x + x2 = 0 Solving 6 + -7x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -1x)(6 + -1x) = 0Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {1, 6}
| (7x^5-8x)(6x^2)= | | -2+5(x-4)=12x+5-7x | | x-2/31/2 | | -6x+6=-2-18 | | 2lnx=ln(2x+9)+3 | | 1/3÷2/3 | | Sin52=x/30 | | -19x^2+49x-30=0 | | -4(y-1)+3y=4(y-4) | | 3-5=3.5 | | 5u+9=109 | | 9x+5=x-11 | | F(n)=5+3n | | x-.3x=434 | | 2(2y+9)=20 | | 18+18=36 | | 0,1(x-10)-0,6x=1,5x-4 | | p-(p+8)=7(p-4)+3p | | 4(x-2)=9+4x | | 1.2x-3.44= | | 6x+3=2(3x+7) | | 8x-4=3+7x | | (2X-3)(X+4)=13 | | 6=4+2y | | 81.9=33.76+9.1x | | 72+18=16(36) | | 12*6+3(18-10)+5*3-11=x | | -3x-11=3x+13 | | 8x+12=2(4x+6) | | x+38=-14 | | 12c^2-7c-10= | | 0.5(72)+0.25(36)=36 |